Reciproc blue: the new generation of reciprocation - Ghassan Yared (Ariesdue, 2017)
Aim: This article introduces the Reciproc® blue system and describes the clinical technique with and without creating a glide path. Methodology: The concept of canal preparation with only one mechanical instrument used in reciprocation was introduced several years ago. Studies and clinical research have shown the efficiency and the safety of the Reciproc® instrument in the preparation of the majority of canals without creating a glide path, and in the retreatment procedure. Results: Reciproc® blue, a thermally treated instrument is an improved version of the original Reciproc® instrument; it has an increased resistance to cyclic fatigue and a greater flexibility enabling a safer and smoother canal preparation procedure, and a wider range of clinical applications. Conclusions: This article introduces and describes the clinical technique with which the Reciproc® blue instrument is used, even without the need to create a glide path with manual files before using the mechanical instrument.